Gender Theory and The Influence of Household Dynamics on Child Care and Feeding Practices In Andhra Pradesh - M., Suvarchala; Kilaru, Yamuna (International Journal of Psychosocial Rehabilitation, 2020)
This study explores the intersection of gender theory and household dynamics in shaping childcare and feeding practices in Andhra Pradesh, India. By conducting qualitative and quantitative research methods, including interviews, surveys, and participant observations, the research investigates how traditional gender roles and power structures within households influence decisions related to child nutrition and care. The findings reveal that women, despite being primary caregivers, often lack autonomy in making significant child-rearing decisions due to patriarchal norms and economic dependencies. This lack of agency impacts the nutritional status and overall well-being of children. The study also examines the role of extended family members and community networks in reinforcing or challenging these gendered practices. The insights gained from this research highlight the need for policy interventions that address gender inequalities and empower women to improve child health outcomes. The study contributes to the broader discourse on gender, health, and development by providing a nuanced understanding of the socio-cultural factors influencing childcare and feeding practices in a specific regional context.